Currybang House / Syamsury Umar … [et.al.]. - Umar, Syamsury; Fadzil, Noor Farina; Isik, Chris Herbert; Baral, Puyang (2008)
There are criteria and conditions that have t be fulfilled which require the involvement of effort and precision of producing our goods. Without such conditions, the business cannot run properly and organizational goals will no be achieved. These conditions must be achieved in order for the business to take position in the first place. Firstly, the organization has to attain a business or trade license from related authorities due the organization's location. The organization must be registered and recognized by the particular departments of government in food product.